The Intonation of Focus Utterance in Japanese - Ulfah, Elisa (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2019)
The study describes the characteristics of phonological intonation on focus utterances in Japanese. The research used quantitative design with two Japanese native teachers as the informants. The Data was gotten through speaking method and a recording technique. In this step, the researcher had a direct conversation with the informants who were guided with the list of conversation, then recorded it. The data were then sorted out using computer software PRAAT and were later analyzed. The results of data analysis show that all intonation contours produced by Japanese informants have the same characteristics, which are the intonation of the utterance focus or the most important part of an utterance rises, while the intonation of another utterance that is not the focus or after the focus falls. In general, the intonation of an utterance has one curve, but the existence of utterance focus can result in the change of intonation. The number of focus in an utterance can cause the emergence of several curves. In order to produce intonation that sounds natural or similar to the native speakers, learners must understand about the intonation contours in Japanese, especially the intonation of the utterance focus.